Formulation and In-Vitro and In-Vivo Evaluation of a Mucoadhesive Gel Containing Eugenia Caryophyllata and Cinnamomum Verum for Treatment of Oral Cancer - Ahmad, Md. Gufran; Chakravarthi, Srikumar; Bhagwat, Pooja; Daharia, Anju; Sarsan, Sreedevi; Sudhakarmeesala, Sudhakarmeesala; Arora, Neha; Guria, Tunul; Matta, Yogesh; Kumar, Anand (Journal of Neonatal Surgery, 2025)
Oral squamous mobile carcinoma (OSCC) is a first-rate fitness problem international due to its excessive charge of mortality and the incapacitating aspect results of the conventional treatments like surgical operation, chemotherapy, and radiotherapy. The modern-day studies aims to design and assess an progressive mucoadhesive gel containing bioactive compounds from Eugenia caryophyllata (clove) and Cinnamomum verum (cinnamon) for the locoregional remedy of OSCC. These natural compounds are properly installed in the literature for his or her anticancer sports, inclusive of cytotoxicity, induction of apoptosis, and inhibition of tumor boom. The drug delivery device became carefully optimized to offer suitable mucoadhesion, sustained launch, and biocompatibility, with an goal to maximize healing effectiveness and reduce systemic toxicity. In vitro analyses decided the cytotoxicity of the gel in opposition to oral most cancers cellular traces, which exhibited large tumoricidal activity, while in vivo preclinical testing confirmed its efficacy in reducing tumor volume without dropping the capacity to hold the drug. The outcome discovered that the method of the gel exhibited improved drug launch over a protracted length, more desirable permeation, and extra therapeutic gain, rendering it a capacity alternative for focused OSCC therapy. This research highlights the promise of plant-derived bioactive formulations in most cancers treatment, imparting a safer and extra green method for oral malignancies management